2019
DOI: 10.15171/apb.2019.054
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Modulation of CHO-K1 Cells Under Genistein Treatment Correlates with Cells Senescence, Apoptosis and ROS Level but in a Dose-Dependent Manner

Abstract: Purpose: Genistein, a soy isoflavone, exhibits a biphasic effect on cells proliferation with some different effects between ER-alpha and ER-beta. The objective of this present study is to determine the modulatory effect based on cell cycle progression under genistein treatment in combination with 17-β estradiol (E2) on CHO-K1 cells. Methods: The effect of genistein 0.1-100 µM on cells proliferation was examined by MTT assay. The modulation of genistein and estradiol (E2) on cell cycle and apoptosis were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 36 publications
1
19
0
1
Order By: Relevance
“…A single treatment of CSP and DOX individually possessed strong cytotoxic effect with dosedependent manner and the low dose of DOX induced lamellipodia elongation. This phenomenon supports the previous studies that DOX in concentration of 10 nM induced lamellipodia formation through the activate transforming growth factor beta (TGFβ) signaling pathway [9], [22]. The activation of TGFβ induces EMT caused inducing motility of cell and metastatic [8].…”
Section: Discussionsupporting
confidence: 91%
“…A single treatment of CSP and DOX individually possessed strong cytotoxic effect with dosedependent manner and the low dose of DOX induced lamellipodia elongation. This phenomenon supports the previous studies that DOX in concentration of 10 nM induced lamellipodia formation through the activate transforming growth factor beta (TGFβ) signaling pathway [9], [22]. The activation of TGFβ induces EMT caused inducing motility of cell and metastatic [8].…”
Section: Discussionsupporting
confidence: 91%
“…where D 1 and [Dx] 1 are concentrations of CL Rhizome and PN herbs, respectively, which inhibit cell growth to 50% of control when used alone, and D 2 and [Dx] 2 are concentrations of CL rhizome and PN herbs, respectively, which have the same effect when used in combination [33]. Combination index values based on the Chou-Talalay method, calculated using CompuSyn software, indicate the effects of drug combinations [34], [35].…”
Section: Analysis Of Combination Activitymentioning
confidence: 99%
“…Similar results were performed by previous studies in which reported (Tamura et al, 2009;Usui et al, 2004) that pironetin (have a similar structure with hyptolide) could inhibit the growth of HT1080 and 3Y1 cells by apoptosis induction. The apoptosis induction on ER-positive breast cancer cells is due to the role of ER in inhibiting cell growth (Jenie et al, 2019;Rouhimoghadam et al, 2018). According to this finding, cell viability response that under hyptolide treatment showed a dose-dependent phenomenon and most of the cell deaths occurred predominantly through apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking the action of estrogen has been shown to reduce breast cancer proliferation and incidence in high-risk women by 50%-75% (Lewis-Wambi and Jordan, 2009;Tian et al, 2018). The previous study also found that estrogen administration causes breast cancer while antiestrogen prevents it (Hollingsworth et al, 1998;Jenie et al, 2019). Those findings provide compelling evidence that estrogen and ER have a significant role in the progression of breast cancer.…”
Section: Introductionmentioning
confidence: 88%